Student’s perceptions and feedback about teaching-learning pharmacology in Nepalgunj Medical College of Chisapani, Nepal - Dhami, Dabal B.; Rathor, R. S.; Bhargava, V. K.; Neupane, Ganesh; Singh, Ritesh; Singh, Ankita (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Pharmacology, being both basic and applied science, forms the backbone of rational therapeutics in medical field. Understanding of current perceptions and opinions of medical students is important for the betterment of teaching-learning methodologies in pharmacology subject. This study done with the objective to determine the perception and feedback of teaching learning pharmacology. Methods: Descriptive cross sectional questionnaire based study was conducted in Nepalgunj Medical College Chisapani, Banke Nepal, among second year MBBS students in September 2017. A questionnaire distributed in class and then collected. Data was analysed using the Statistical Package for Social Sciences (SPSS). Results: Total 119 students, 78 male and 41 females participated in this study. The percentage average of agreed responses for 15 questions (58.92±19.53) was significant (p <0.05) when compared with the percentage average of the disagreed (5.42± 5.17). Seventy three (61.3%) students agreed that pharmacology is a favourite subject but the preferences for pharmacology as a subject in post-graduation was low (18.5%). High proportion of students wanted the faculty members to make more use of Audio-Visual aids 93.3%, case based learning 96.6%, more clinical pharmacology, 97.5%, group discussions, 88.2%, integration to clinical sciences 92.4% and 82.4% prefer MCQs to be introduced in the curriculum for effective learning. Conclusions: Introduction of integrated teaching, MCQs, case based, and group based discussion with clinical pharmacology and audio-visual aids was favoured by majority of the students. Regular reviewing perception and feedback of the students help teachers to plan the curriculum and improve the teaching methodologies.